Respon Pertumbuhan dan Produksi Tanaman Cabai Rawit (Capsicum frutescens L) terhadap Pemberian Kompos dan Biochar dari Limbah Ampas Tebu - Ilyasa, Muhammad; Hutapea, Sumihar; Rahman, Abdul (Universitas Medan Area, 2018)
The purpose of this research is to know the growth response and the production of cayenne pepper (Capsicum Frutescens L.) to the composting and biochar which is taken from the waste of bagasse, then compared with the growth response and the production of cayenne plant using inorganic fertilizer. The method used. The research was conducted in experimental garden of Faculty of Agriculture, University of Medan Area, located at No. Pond Street. 1 Medan Estate, Percut Sei Tuan District. The research method used Factorial Randomized Block Design (RAK), with three replications, 12 combinations to obtain 36 plant plots of all combinations and replications. The first factor tested was Biochar bagasse ie Bo = without biochar, B1 = given Biochar 4 ton / ha and B2 = given Biochar 8 ton / ha. The second factor tested was compost of bagasse waste that is K0 = without compost of bagasse, K1 = composted 10 ton / ha, K2 = given 15 ton / ha and K3 = composted 20 ton / ha. The results showed that the influence of compost combination (K3 = 20 tons / ha) was more influential on all observation parameters compared to biocar with best combination of B2K3, B1K3 and B0K3. In general, this study showed that the addition of biochar of bagasse and kmpoos of bagasse in the cultivation media of cayenne pepper can increase the growth and production of pepper cayenne plants with more economical production cost.